New Stability Indicating RP-HPLC Method for the Estimation of Budesonide in API and Pharmaceutical Dosage Forms - Yamani, N. S. (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Budesonide is used for the treatment ofchronic obstructive pulmonary diseaseand asthma, and it belongs to glucocorticoid class. A new stability indicating RP-HPLC method has been proposed for the quantification of Budesonide in tablet dosage forms and the method was validated. Materials and Methods: Shimadzu HPLC system with PDA detector was used with Agilent C18 column with mobile phase mixture, formic acid: Methanol (30:70) and flow rate 1.0 ml/min (UV detection at 243 nm). Results and Discussion: Beer-Lambert’s law was obeyed over a concentration range 0.1–100 μg/ml. The linear regression equation was found to be y = 48625x + 8107.9 (r2 = 0.9998). The LOD and LOQ were found to be and 0.0302 and 0.0922 μg/ml. Stress degradation studies were performed and the method was validated as per ICH guidelines. The proposed method is simple, precise, accurate, and robust and can be applied for the assay Budesonide formulations.